(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
With the common goal of reaching commercial viability and utility-scale deployments of wave and tidal projects, it is necessary to consider the potential of earning revenues by participating in the regional and international electricity markets. Countries have agreed on binding goals of reducing their emissions and planned installations of renewable energy generation plants of considerable sizes. Their focus lies on constructing large-scale power plants using mature technologies (such as photovoltaic panels and wind turbines) which leads to a limited number of renewable energy resources (solar irradiance and wind) having a strong dependency and influence on the total electricity generation. The effect of the future projected outbuild of renewable energy on the energy mix of counties and regions cannot be neglected and its ramifications on the electricity market need to be quantified and assessed. The expected changes in electricity price will affect renewable energy parks differently based on their power production patterns. While different market and policy mechanisms are being introduced with the aim to soften the impact on power prices it is inevitable that a fully renewable energy system will be driven by peaks and valleys in renewable production. To study the changes in expected electricity prices in the future energy mix, a previously introduced methodology has been updated to simulate the electricity market behaviour based on the residual load which is defined as the difference between the cumulative electricity produced from renewable energy sources and the demand of the market region. The methodology is based on the linear relation between total residual load and recorded electricity prices observed and studied in historical datasets concluding a linear regression between the two parameters. Initially, the total power generated by renewable energy parks in the assessed geographical region is calculated as an hourly time series. For this historical resource data is applied combined with planned capacities of onshore and offshore wind and onshore PV farms. Similarly, the total demand time series is calculated by using historical demand data and scaling it to fit the future scenario. These two parameters are used to calculate the total residual load in the energy system. Assumptions are made for the values of future marginal costs of renewable and non-renewable technologies generating electricity to define the linear regression line and calculate the electricity market price time series. The methodology is validated with historical data from 2023. Each technology included in power generation farms operating on the electricity market (e.g. offshore wind turbines or wave energy converters) is assessed separately to provide information on their respective captured electricity prices. These results can be used to identify regions in which the market structure will benefit wave and tidal energy technologies specifically. This can be either due to a high complementarity of the wave or tidal resource with the locally prevalent renewable energy source, or due to specific regional demand profiles.